Credit Risks and Capital Risks and their impact on Banking Liquidity, Applied Research in al-Mansour Investment Bank and the Iraqi Investment Bank - Ali Abdulamer Kadhim; Ahmed jamal kadhim; Akeel Dakheel Kareem (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
The research aims to shed light on the variables of the study, credit risks and capital risks, and provide an introductory framework for them and the theoretical relationship with the dependent variable on banking liquidity, and then measure those risks on commercial banks (Al-Mansour Investment Bank and the Iraqi Investment Bank) and then find statistical relationships between the variables The independent and dependent variable and then using the statistical analysis program (SPSSv.26) to find the effect relationship of credit risk and capital risk on bank liquidity. One of the most important conclusions reached by the researchers is that there is a relationship between credit risks when they rise on bank liquidity, and this is explained by the value of the correlation between credit risks and bank liquidity in commercial banks, the study sample (.957**) at a significant level (0.01). There is a relationship. between capital risks when they rise on bank liquidity, as the value of the correlation between capital risks and bank liquidity in the study sample commercial banks was (-.873**) at a significant level (0.01).